Clinical evaluation of class II composite resin restorations placed by two different bulk- fill techniques - KURDI, Rahaf; ALI ABBOUD, ALI ABBOUD (International Arab Journal of Dentistry (IAJD), 2016)
The purpose of the present study was to compare the clinical performance of class II composite resin restorations using two different bulk fill techniques according to the United States Public Health Service criteria (USPHS) over 12 months follow-up. Sixty class II restorations were placed in 60 patients, 20-50 years old. The patients were divided into three groups according to the applied restoration technique. In all cavities, etching (N Etch, Ivoclar Vivadent) was applied for 15 seconds and then rinsed. After that bonding was applied and cured for 20 seconds (N Bond, Ivoclar Vivadent). In group 1, Tetric Evo Ceram (Ivoclar Vivadent) was placed in 2 mm increments. In group 2, Tertic N Ceram Bulk Fill (Ivoclar Vivadent) was placed in single increment. In group 3, SonicFill™ (Kerr, Kavo) was placed in single increment by sonic vibration. The restorations were evaluated using modified USPHS criteria at baseline and then after 3, 6, 9 and12 months. After 12 months, 58 class II restorations were evaluated. Two cases were dropped out. All the restorations in the three groups showed acceptable clinical performance according to the modified USPHS criteria. The differences between the techniques weren’t statistically significant. Overall success was 91.3%. Five restorations failed, one in the first group and four in the second group. Both bulk fill techniques performed well over the 12 months observation period. The bulk fill composite resin performed equally to the conventionally layered resin composite during the 12 months of the present clinical study.